Report on professional attachment with Citibank - Wong, Kai Leong (2014)
The purpose of this report is to give a clear, detailed and precise explanation of my work was well as my job experience with Citibank. In this report, I will give an introduction on the company and its businesses. Then I will talk about the work that I had to do, how i went about doing it, and the results of my findings. I will also talk about the people I work with, and the work that they do.